CHARACTERISTICS OF ANOPHELES BREEDING PLACES IN DAHIAN TAMBUK VILLAGE, GUNUNG MAS DISTRICT, CENTRAL KALIMANTAN - Tasya Zahrawana, Mouldy; Mutiasari , Dian; Ratnasari, Arini; Jabal, Arif Rahman; Triawan, Nopta; Kurniawan, M. Yusuf Ilham; Djajanto, Marchelia; Karmila, Mila (Journal of Vocational Health Studies, 2024)
Background: Malaria cases in Dahian Tambuk Village have been ranked first for four consecutive years in Gunung Mas District. Purpose: This study aims to describe the physical and chemical characteristics of Anopheles breeding places in Dahian Tambuk Village, Gunung Mas District. Method: It is a descriptive study using a survey method. The characteristics studied were Anopheles species, number, temperature, salinity, breeding sites, and density of larvae found in each breeding site. Result: Seven breeding places were found positive to contain Anopheles larvae, consisting of puddles, fish ponds, and sewers. The sewer was predominantly found. Physical characteristics of water showed a temperature ranging from 29.9 0C - 35 0C, pH levels between 5.35 - 6, and a salinity of 0 ppt, with a density level of 9 larvae/2 dippers. The species of Anopheles larvae found in all breeding sites was identified as Anopheles kochi. Conclusion: Seven breeding sites found in the studied area consisted of puddles, fish ponds, and sewers, with physical characteristics that qualify for Anopheles larvae in general An. kochi was the only species of larvae found in all breeding sites.